2022
DOI: 10.1155/2022/9394382
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Factors Influencing Government Control Rights in PPP Projects from the Perspective of Investors

Abstract: The information resources owned by the government cannot be completely defined due to the incompleteness of the PPP contract. These information resources influence investors’ judgment on the government’s control rights, thus influencing the fair cooperative relationship and rational decision-making. In order to analyze the criteria for investors to evaluate the government’s control rights in PPP projects in the process of decision, 14 factors that influence the government’s control rights are identified throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…De acuerdo a Liu et al (2022), al investigar sobre el impacto de los riesgos de control en las inversiones PPP (Public-Private Partnerships o Asociaciones Públicas Privadas), la razón de riesgo tiene la mayor influencia en derechos explícitos de control, seguido por el índice de equidad. El estatus del gobierno tiene la mayor influencia sobre los derechos de control implícitos, ello porque en China a diferencia de nuestra región las instituciones tienen más claro el rol que les toca desempeñar en las relaciones contractuales con el sector privado.…”
Section: Modalidades De Control Interno Y Su Efectividad Contra La Co...unclassified
“…De acuerdo a Liu et al (2022), al investigar sobre el impacto de los riesgos de control en las inversiones PPP (Public-Private Partnerships o Asociaciones Públicas Privadas), la razón de riesgo tiene la mayor influencia en derechos explícitos de control, seguido por el índice de equidad. El estatus del gobierno tiene la mayor influencia sobre los derechos de control implícitos, ello porque en China a diferencia de nuestra región las instituciones tienen más claro el rol que les toca desempeñar en las relaciones contractuales con el sector privado.…”
Section: Modalidades De Control Interno Y Su Efectividad Contra La Co...unclassified
“…In addition to formal coordination, this cooperation must also be built on mutual trust between the two sectors. Previous studies have indicated that investors' levels of trust are a significant element in determining whether or not they will participate in a particular investment transaction (Kim et al, 2018;Liu et al, 2022;Xu et al, 2022). Indeed, Akhtar and Das (2019) stress that trust influences an investor's decision to invest.…”
Section: Trust In Government and Investor Decision On Pppmentioning
confidence: 99%